Exploring the Trends and Methods of Neo-Orientalism (Al Basirah, 2025)
Neo-Orientalism signifies a contemporary reconfiguration of classical Orientalist discourse, operating through modern political, cultural, and artistic matrices. This study critically investigates how visual culture including painting, photography, fashion imagery, filmic representations, and digital media continues to circulate Orientalist tropes through nuanced strategies of exoticism, symbolic reduction, and the commodification of Muslim identities. In the post-9/11 global landscape, such representations frequently recast Muslims as exotic, regressive, or inherently threatening, thereby sustaining a visual vocabulary rooted in colonial epistemologies. Employing a qualitative and comparative visual analysis of selected artistic works and media outputs, the research delineates the methodological patterns, aesthetic mechanisms, and ideological functions underpinning Neo-Orientalist imagery. The scope encompasses dominant Western artistic productions alongside counter-narratives generated by contemporary Muslim, diaspora, and decolonial artists. These counter-practices challenge hegemonic framings by reclaiming visual agency, confronting misrepresentation, and constructing alternative epistemic spaces. The findings demonstrate that Neo-Orientalism persists through renewed aesthetic techniques and globalized modes of dissemination; however, it is increasingly met with powerful artistic interventions that destabilize, reinterpret, and contest Orientalist assumptions. Consequently, the study reveals a dynamic visual field in which colonial residues and critical resistances coexist, shaping the evolving discourse of representation in the twenty-first century.Conflict of Interest: The authors declare that there are no conflicts of interest related to the research, authorship, and/or publication of this article, and that the data presented have not been fabricated or falsified.Funding: This research did not receive any specific grant or financial support from public, commercial, or not-for profit funding agencies.Participant Consent:  The authors confirm that Informed consent was obtained from all participants, and confidentiality was duly maintained.Data Fabrication/Falsification Statement: The author(s) declare that no data have been fabricated, falsified, or manipulated in this study.Copyright: Author(s) retains the Copyright of this article.
Keywords: Neo-Orientalism; Orientalism; Art; Visual Culture; Representation; Postcolonial Art; Muslim Identity; painting; Exoticism